A Need Of Sharī ‘ah Compliant Model Of 3d Bioprinting - Nurmunirah Ramli; Mohammad Naqib Hamdan; Mohd Anuar Ramli; Saiful Izwan Abd Razak; Mohd Farhan Md Ariffin; Hussein 'Azeemi Abdullah Thaidi (University of Management and Technology (UMT), 2024)
Indexed by SCOPUS